Use of Direct‐to‐Consumer Telemedicine: A Qualitative Study Exploring the Thoughts, Perspectives and Experiences of Australian Adults - Andrew Turner; Kate Churruca; Samantha Spanos; Thomas Courtney‐Stubbs; Darran Foo; Louise A. Ellis (Health Expectations, 2026)
ABSTRACT Introduction Following the COVID pandemic, direct‐to‐consumer (DTC) telemedicine services that offer medical expertise via remote electronic interfaces have surged in popularity. This paper explores the perspectives and experiences of patients using DTC telemedicine services in Australia, including their perceptions of benefits, concerns and interactions with traditional general practice. Methods This was a qualitative study using semi‐structured interviews, which were recorded and transcribed. Thematic analysis was conducted using NVivo, with a combination of inductive and deductive coding. Participants were recruited from a previous survey on user experiences with up to five different DTC telemedicine services. Results Thirteen participants had experience with DTC telemedicine services for women's health, skin care, men's health and women's fertility. Four themes were identified: (1) Convenience, efficiency and greater access —flexible appointment scheduling, reduced wait times and the online user interface were major benefits of DTC telemedicine services. Participants also highlighted the capacity of DTC telemedicine to enhance healthcare accessibility for those living rurally or with mobility challenges; (2) The value of anonymity —DTC telemedicine facilitated care for potentially stigmatised conditions such as obesity and erectile dysfunction, encouraging some patients to seek care they might otherwise avoid; (3) Concerns about inappropriate use of medication —participants questioned whether ease of access might lead to inappropriate prescribing, and (4) Interactions with general practice —DTC telemedicine was perceived as more of a supplement to general practice rather than a replacement. Despite this, participants indicated that negative experiences with GPs contributed to DTC telemedicine use. Conclusion DTC telemedicine was viewed as a convenient and efficient alternative to general practice for certain health issues. However, concerns were identified regarding prescribing safety, continuity of care and inequity in access. If regulatory gaps are addressed, collaboration with GPs improved and disparities in access minimised, DTC telemedicine has the potential to play a complementary role in strengthening Australia's primary healthcare system. Patient and Public Involvement This research was undertaken in partial fulfilment of the requirements of a Doctor of Medicine program. Given the timeframe allotted for undertaking this research, formal PPIE was not possible. However, two members of the research team had experience using the services discussed in this study and drew upon these experiences in developing interview questions and interpreting findings.